Decarbonisation and financial performance of energy companies - Ágnes Horváth; Adrienn Takács Papp; Katalin Lipták; László Molnar; Klára Szűcs Markovics; Ioana Manafi; Zoltán Musinszki (Amfiteatru Economic)
Our daily lives are unimaginable without energy. Producing it, however, may be harmful to the environment depending on the energy source. The Paris Agreement brought a key question to the fore: with or without coal? The Powering Past Coal Alliance (PPCA) members, including the European Union, have committed to the phasing out of coal by 2030. Several Member States of the European Union have recently closed almost 130 coal-fired power plants. The closure of these plants, in addition to impacting greenhouse gas (GHG) emissions, also exerts influence on the financial position of power plant owners. This study seeks to answer the question of how the profitability of the company groups that operate (and have closed) coal-fired power plants in the European Union has evolved. Is there a relationship between decarbonisation and profitability trends, and are there any patterns in the environmental and financial performance of individual company groups? The main added value of our research is highlighting that different groups of companies have responded differently to the EU’s decarbonisation targets, and these reactions have also been reflected in their financial performance. The study included 21 company groups that cover more than 70% of CO2 emissions from coal-fired power plants in the EU. The profitability indicators were calculated based on the publicly available consolidated annual reports of the companies for 2016 and 2020. Following a reliability test of the indicators, a cluster analysis was carried out. The different reactions allowed us to classify the energy groups into different clusters. The analysed companies were classified into four homogeneous groups: Frontrunner, Up-and-coming, Sacrifice makers, and Stagnating companies. Although a significant relationship could not be found between the change in GHG emissions and the change in profitability position, a multidirectional relationship was identified between the environmental and financial performance of companies.